The Profit Distribution of Supply Chain under E-Commerce - Jiang-Hua Zhang; Rui-Rui Yin; Jin Zhang; Meng-Jiao Nie (Discrete Dynamics in Nature and Society)
With the development of e-commerce, its influence on supply chain and supply chain management is becoming increasingly significant too. In this paper, the literature on the supply chain profit is reviewed first, and then a two-level and four-party supply chain which consists of a supplier, an e-commerce platform, third-party logistics, and demander is taken into consideration. The profit function of supply chain under e-commerce is formulated by taking the price of product and the maximum supply amount under certain investment as decision-making variables and taking the expected value of random variables of price as the setting sales quantity. Finally, the existence of maximum profit in the supply chain is proved in the model, and the coordination of supply chain under e-commerce environment can be achieved by setting coordination parameters when the relevant cost parameters of supply chain members satisfy certain conditions.